A comparison of the adomian and homotopy perturbation methods in solving the problem of squeezing flow between two circular plates - Siddiqui, Abdul M.; Haroon, Tahira; Bhatti, Saira; Ansari, Ali R. (Mathematical Modelling and Analysis, 2010)
The objective of this paper is to compare two methods employed for solving nonlinear problems, namely the Adomian Decomposition Method (ADM) and the Homotopy Perturbation Method (HPM). To this effect we solve the Navier‐Stokes equations for the unsteady flow between two circular plates approaching each other symmetrically. The comparison between HPM and ADM is bench‐marked against a numerical solution. The results show that the ADM is more reliable and efficient than HPM from a computational viewpoint. The ADM requires slightly more computational effort than the HPM, but it yields more accurate results than the HPM.First published online: 10 Feb 2011